2007
DOI: 10.1111/j.1469-8137.2007.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of plant defence response by a mycorrhiza helper bacterium

Abstract: Summary• The aim of the present study was to determine whether the mycorrhiza helper bacterium Streptomyces sp. AcH 505 could serve as a biocontrol agent against Heterobasidion root and butt rot.• Bacterial influence on mycelial growth of Heterobasidion sp. isolates, on the colonization of wood discs and Norway spruce ( Picea abies ) roots was determined. The effect of AcH 505 on plant photosynthesis, peroxidase activity and gene expression, and needle infections were investigated.• AcH 505 was antagonistic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 45 publications
1
56
0
1
Order By: Relevance
“…According to literature, the infection of Norway spruce with Heterobasidion annosum is associated with a plant defence-related increase in peroxidase activity and PaSpi2 peroxidase and PaChi4 chitinase gene expression levels (Asiegbu et al 1993;Fossdal et al 2001;Hietala et al 2004). Instead, we observed decreased expression of these defence markers after AcH 505 inoculation of the plant (Lehr et al 2007). This indicates that AcH 505 suppresses important components of the plant defence response against Heterobasidion.…”
Section: Growth Factors and Cell Stress: Complex Interactions Betweenmentioning
confidence: 78%
See 2 more Smart Citations
“…According to literature, the infection of Norway spruce with Heterobasidion annosum is associated with a plant defence-related increase in peroxidase activity and PaSpi2 peroxidase and PaChi4 chitinase gene expression levels (Asiegbu et al 1993;Fossdal et al 2001;Hietala et al 2004). Instead, we observed decreased expression of these defence markers after AcH 505 inoculation of the plant (Lehr et al 2007). This indicates that AcH 505 suppresses important components of the plant defence response against Heterobasidion.…”
Section: Growth Factors and Cell Stress: Complex Interactions Betweenmentioning
confidence: 78%
“…This indicates an important application for MHB such as AcH 505: the simultaneous growth promotion of mycorrhizal as well as growth suppression of pathogenic fungi (Schrey et al 2005). To investigate this possibility, Lehr et al (2007) conducted a screening of 12 plant pathogenic isolates of Heterobasidion in dual culture with AcH 505. All but one of the Heterobasidion strains were suppressed by AcH 505.…”
Section: Growth Factors and Cell Stress: Complex Interactions Betweenmentioning
confidence: 98%
See 1 more Smart Citation
“…Streptomycetes soil produce hydroxamate-type siderophore, could inhibit plant pathogens growth and thus reduce their action by competing for the phenomenon for iron [27]- [29]. Or by stimulation of plant defenses [30]- [33]. Thus, the results obtained in this study on Fusarium soft wheat will contribute positively to the improvement of biocontrol process against these diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Although several authors have shown the effectiveness of these microorganisms as biological plant disease control agents (Shekhar et al 2006;Lehr et al 2008), very few reports involve forest species (Lehr et al 2007).…”
Section: Introductionmentioning
confidence: 99%